PERHITUNGAN PRODUKTIVITAS DAN ESTIMASI WAKTU PENGECORAN KOLOM MENGGUNAKAN TOWER CRANE - , ZULFI NIHAYATUN N ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Analysis of Tower Crane productivity is very important to determine the ability of Tower Crane to produce something. Tower Crane is an important factor in the construction projects rise buildings with large scale implementation of the project and construction is expected to be achieved more easily in a relatively short time . As for some of the factors that affect the productivity of Tower Crane, among others, the condition of the tool, field conditions, management factors, the ability of the operator. In the use of Tower Crane difficult finding a tool that is 100% condition. Always there is a decrease in productivity tools Tower Crane, and the resulting increase in the duration of the work that resulted in the execution work effectiveness in the implementation of the multi-storey building construction work. Thus, it can be concluded that productivity is the ability to produce something, which can affect the time and work effectiveness in the execution of the work. Results productivity of 6.67 tonnes / hour and the estimated time of the appointment of 0.576 hours.